The Influence of Entrepreneurial Leadership on the Performance of ngineering SMEs Mediated by Interpersonal Communication and Entrepreneurial Characteristics - Nandang Nandang; Disman; Janah Sojanah; Hady Siti Hadijah (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
The study aims to analyze the effect of entrepreneurial leadership on SME performance, evaluate the mediating role of interpersonal communication, and assess the contribution of entrepreneurial characteristics in strengthening the relationship between leadership and performance. A quantitative approach with an explanatory survey design was employed, with data collected through questionnaires distributed to owners, managers, or leaders of engineering SMEs in Karawang Regency and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables. The findings indicate that entrepreneurial leadership has a significant influence on entrepreneurial characteristics, which subsequently mediate the effect of leadership on SME performance, while interpersonal communication contributes positively to performance but is not proven to mediate the relationship between leadership and performance. Entrepreneurial characteristics are identified as the dominant factor in improving SME performance. Theoretically, this study reinforces the central role of entrepreneurial characteristics in the mechanism linking leadership and performance, while practically, the findings provide a foundation for the development of training programs, mentoring strategies, and capacity-building initiatives aimed at enhancing competitiveness, innovation, and business sustainability of SMEs in the engineering sector.